Pituitary Stalk Interruption Syndrome: A Case and Literature Review - Anuja Choure, MD; Leena Shahla, MD (AACE Clinical Case Reports)
Background/Objective: Pituitary stalk interruption syndrome (PSIS) is a rare congenital disorder that is characterized by a triad including a thin or interrupted pituitary stalk, absent or ectopic posterior lobe, and agenesis or dysgenesis of anterior lobe.PSIS is typically diagnosed in childhood. The objective of this report is to describe a patient with PSIS whose diagnosis was missed until adulthood. Case Report: A 42-year-old-female presented for evaluation of premature menopause, weight loss, and occasional dizziness. On examination she had short stature and absent secondary sexual features. Laboratory tests were consistent with hypopituitarism with follicle stimulating hormone 0.5 mIU/mL (16.7-113); luteinizing hormone 1.2 mIU/mL (10.8-58.6); prolactin 10.4 ng/mL (2.7-19.6); estradiol 20 pg/mL; cortisol 2 mcg/dL (6.7-22.6); adrenocorticotropic hormone 18 pg/mL (6-50); thyroid stimulating hormone 10.33 uIU/mL (0.28-3.8); free T4 0.41 ng/dL (0.58-1.64); insulin like growth factor-1 −3.7 SD (17 ng/mL) (52-328); and adrenocorticotropic hormone stimulation confirmed secondary adrenal insufficiency. The magnetic resonance imaging of the brain revealed an ectopic posterior pituitary with a partially empty sella, absence of the pituitary stalk, and a small anterior pituitary. The patient was initiated on replacement hormones with improvement in her symptoms. Discussion: PSIS is a rare condition with uncertain pathogenesis and variable presentation requiring a high index of suspicion and presenting with multiple anterior pituitary hormone deficiencies. Diagnosis is confirmed by a dedicated pituitary magnetic resonance imaging, and treatment is tailored to the hormonal deficiency detected. Conclusion: This case highlights the importance of early diagnosis of PSIS, which presents with multiple anterior pituitary hormonal deficiencies, but diagnosis can remain elusive unless dedicated brain imaging is performed.